ANALISIS KEBUTUHAN BAHAN AJAR MATEMATIKA SISWA KELAS V SDN KEPANJENLOR 1 - Latifah, Lia; Zainuddin, Mohammad; Surayanah, Surayanah (Wahana Sekolah Dasar, 2023)
The purpose of this study was to find out the teaching materials needed in class V SDN Kepanjenlor 1 on Mathematics content. The research method used is qualitative, so the data is obtained through filling out questionnaires and interviews. The results of the research obtained were that teachers needed teaching materials to accompany the Mathematics content on addition and subtraction of fractions which included practice questions and their solutions related to everyday life. The results of the questionnaire obtained a percentage of 81%, meaning that most students needed Mathematics teaching materials. The teaching materials needed by students are technology-based teaching materials which are equipped with videos, pictures and practice questions. Keywords: mathematics; needs analysis; teaching materials